Clinical forms of acute intestinal obstruction, choice of surgical intervention, postoperative management. (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
this article includes clinical forms, postoperative management and choice of the most surgical intervention for patients with acute intestinal obstruction.